2011
DOI: 10.1016/j.jvs.2010.11.110
|View full text |Cite
|
Sign up to set email alerts
|

Coil embolization of persistent false lumen after stent graft repair of type B aortic dissection

Abstract: Patent false lumen after endovascular stent graft treatment of type B aortic dissection is a predictor for late death and retreatment. Between June 2008 and March 2010, five men with patent false lumen, due to a type B dissection previously treated with thoracic stent graft, underwent endovascular coiling treatment. Within a 30-day period, there were no deaths or major complications. The follow-up duration ranged from 1 to 22 months (mean 10.6 ± 8.5). Endovascular coiling of patent false lumen after endovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…[34][35][36] Repairing all entry tears might benefit selected patients, which involves a question whether all entry tears should be repaired at the initial therapy. Management of distal entry tears in type B aortic dissection should be individualized according to the dissection anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] Repairing all entry tears might benefit selected patients, which involves a question whether all entry tears should be repaired at the initial therapy. Management of distal entry tears in type B aortic dissection should be individualized according to the dissection anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…Norberto et al 19 and Pellenc et al 20 showed that thrombosis of the false lumen after TEVAR for TBAD promotes aortic remodeling. Watanabe et al 21 showed that aortic remodeling after TEVAR decreases the risk of aortic adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Norberto and colleagues [8] introduced the FL coil embolization technique as the subsidiary treatment for patients who primarily underwent stent graft repair of type B dissection. However, unlike their case reports, our case introduces a primary aortic pathology correction through the FL tract by entering the reentry tract that was located at the ascending aorta.…”
Section: Commentmentioning
confidence: 99%